Basic rheology of dermal filler - Moon Seop Choi (Archives of Plastic Surgery, 2020)
Dermal injectables are the most popular material for facial enhancement, including volumizing and wrinkle correction. However, although hyaluronic acid is the most common component of dermal injectables, the character of hyaluronic acid products is quite variable. These materials can be described in terms of their viscoelastic properties using four parameters. In this article, the author would like to describe these properties in detail. Although many physicians consider this material to be convoluted, thoroughly understanding the characteristics of various injectables enables us to tailor procedures accordingly and to enhance the final results.